ART PRACTICE AT THE TIME OF THE PROPHET: Literature and Fine Arts from Qabla Risalah to Fathu Makkah - Irawan MN, Aguk (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2019)
The Qur’an is the highest law book used to understand Prophet Muhammad’s prophetic mission. Therefore, the social conditions of the community need to be analyzed before and after the treatise to obtain an extraordinary level of artistic appreciation. This paper limits the study of poetry and fine arts as a branch of philosophy, using a historical-analytical approach following the shift theory of Talal Asad’s model. The use of this approach, from the period of the qabla risalah (before the arrival of Islam) to fathu Makkah (conquest of Mecca), led to changes in the form of genre and function of art; a shift from pragmatism-hedonism to idealismpost-impressionism for poetry, and from sacred realism-naturalism to desacral ornamental-cubism for the fine arts.